Исследование зависимости характеристик пьезоэлектрических преобразователей от конструктивных параметров - Иващенко, С. А. (ХНУРЭ, 2012)
The purpose of this paper is the mathematical modeling of the characteristics of piezoelectric elements with improved design parameters and characteristics. The advantages of piezoelectric transducers are high linearity, wide dynamic and frequency ranges, design simplicity and high reliability in operation, small size and cost.
Keywords: пьезоэлектрические преобразователи; математическое моделирование; конструктивные параметры